If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -48 = 5x + 27 Reorder the terms: -48 + 11x = 5x + 27 Reorder the terms: -48 + 11x = 27 + 5x Solving -48 + 11x = 27 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -48 + 11x + -5x = 27 + 5x + -5x Combine like terms: 11x + -5x = 6x -48 + 6x = 27 + 5x + -5x Combine like terms: 5x + -5x = 0 -48 + 6x = 27 + 0 -48 + 6x = 27 Add '48' to each side of the equation. -48 + 48 + 6x = 27 + 48 Combine like terms: -48 + 48 = 0 0 + 6x = 27 + 48 6x = 27 + 48 Combine like terms: 27 + 48 = 75 6x = 75 Divide each side by '6'. x = 12.5 Simplifying x = 12.5
| 56=8/5m | | 4r+2=3r-5 | | 03249349049804890904+309248902490=34039024923490039249023904920949090409203940092099409049034 | | 6p+p-q+8q= | | -5/7-3/5 | | 8x-12=2-24 | | -3(3v+2)=-33 | | x(x-1)=14 | | 2242.7136=578.7648+60.288h | | 11x-38=3x+41 | | 12x^3-15x^2-35=0 | | 1945.0416=497.4388+55.892h | | 5x+9=11x+7 | | 2x/28=100 | | X-2b=0 | | 4d+5=3d-7 | | (3+I)(4+2i)= | | -6(2x+2)=12 | | n^4-53n^2+196=0 | | a=x-2-2(3x+2)+(6x+5) | | 4c-3=2 | | 2x+3x+57=180 | | 2x^2-2=5 | | [x-10]=5x+10 | | 10(x-5)=-87 | | 2u^2=-7-5 | | 4s+4=5s-2 | | 13.5+x=40.5 | | 7+a=17+3a | | 6x+33=0 | | x^2+y^2=9-8y | | 5y+vx=y^2 |